Salsola soda as selenium biofortification crop under high saline and boron growing conditions - Bañuelos, Gary S.; Centofanti, Tiziana; Zambrano, Maria C.; Vang, Kaomine; Lone, Todd A. (Frontiers in Plant Science, 2022)
In California, there is a shortage of good quality water available for irrigated agriculture due to severe drought. Consequently, saline groundwaters and drainage waters containing natural-occurring selenium (Se) and boron (B) salts are being considered as alternative sources of water for irrigation on salt and B tolerant crops like the edible halophyte-agretti (Salsola soda L.). In this multi-year field study, we evaluated agretti grown as a Se-biofortification crop in typical saline/B-laden soils (10 dS m−1 and 12 mg B/L) and irrigated with saline (3–8 dS m−1) and low-saline water (<1 d/S m) containing B (3–6 mg B/L) and Se (0.02–0.25 mg Se/L) at different evaporation transpiration (Eto) rates (100, 75, and 50 %, respectively). During the four-year study, fresh biomass yields ranged from 1 to 3 kg/m2 and were generally highest with irrigation at 100 % Eto with either saline or low-saline water. Tissue Se concentrations ranged from 2 to 3.2 mg Se / kg DW and 0.4–0.5 mg Se/kg DW with saline and low-saline irrigation, respectively. Selenium speciation in plant tissue showed the following: selenomethionine (SeMet) > selenate (SeO4) > methylselenocysteine (MeSeCys), irrespective of any treatment (i.e., year of planting, saline or low saline irrigation, rate of water application, direct seeding or transplanted). Agretti did not exhibit any toxicity symptoms as indicated by changes in total phenolic concentrations. Total phenolics ranged from 180 to 257 GAE/L and showed no significant differences among all treatments, although they were generally higher at the lowest water treatment (50% Eto). In regard to toxic ion accumulation, agretti tolerated excessive sodium (Na) and boron (B) and tissue concentrations ranging from 5.5 to 8.8% Na and 60 to 235 mg B/kg DW, respectively. Results from this multi-year study have identified a unique Se-biofortification strategy for producing Se-enriched agretti using saline, B- and Se-laden soil and irrigating with saline and low-saline water, respectively. Successful production of this crop may promote Se- biofortification strategies in poor quality regions where natural- occurring Se is present in soils and in waters used for irrigation.